Bio-Refining of Carbohydrate-Rich Food Waste for Biofuels - Hoang-Tuong Nguyen Hao (Energies, 2015)
The global dependence on finite fossil fuel-derived energy is of serious concern given the predicted population increase. Over the past decades, bio-refining of woody biomass has received much attention, but data on food waste refining are sorely lacking, despite annual and global deposition of 1.3 billion tons in landfills. In addition to negative environmental impacts, this represents a squandering of valuable energy, water and nutrient resources. The potential of carbohydrate-rich food waste (CRFW) for biofuel (by Rhodotorulla glutinis fermentation) and biogas production (by calculating theoretical methane yield) was therefore investigated using a novel integrated bio-refinery approach. In this approach, hydrolyzed CRFW from three different conditions was used for Rhodotorulla glutinis cultivation to produce biolipids, whilst residual solids after hydrolysis were characterized for methane recovery potential via anaerobic digestion. Initially, CRFW was hydrolysed using thermal- (Th), chemical- (Ch) and Th-Ch combined hydrolysis (TCh), with the CRFW-leachate serving as a control (Pcon). Excessive foaming led to the loss of TCh cultures, while day-7 biomass yields were similar (3.4–3.6 g dry weight (DW) L−1) for the remaining treatments. Total fatty acid methyl ester (FAME) content of R. glutinis cultivated on CRFW hydrolysates were relatively low (~6.5%) but quality parameters (i.e., cetane number, density, viscosity and higher heating values) of biomass extracted biodiesel complied with ASTM standards. Despite low theoretical RS-derived methane potential, further research under optimised and scaled conditions will reveal the potential of this approach for the bio-refining of CRFW for energy recovery and value-added co-product production.